1994
DOI: 10.1246/bcsj.67.1918
|View full text |Cite
|
Sign up to set email alerts
|

Halogenation Using N-Halogenocompounds. II. Acid Catalyzed Bromination of Aromatic Compounds with 1,3-Dibromo-5,5-dimethylhydantoin

Abstract: Ring bromination of aromatic compounds using 1,3-dibromo-5,5-dimethylhydantoin in dichloromethane is promoted by the addition of strong acids. Both organic and inorganic acids whose pKa values are lower than -2 showed the promoting effect. This acid-catalyzed bromination is both practical and effective, even for aromatics having electron-withdrawing substituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…[3b] Under the somewhat milder version of this procedure, [11] low yields of dibromide 6 were obtained. Selective conditions for the synthesis of monobromide 5 and dibromide 6 in high yields were observed -when pure bromine and a trace amount of iodine were used, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…[3b] Under the somewhat milder version of this procedure, [11] low yields of dibromide 6 were obtained. Selective conditions for the synthesis of monobromide 5 and dibromide 6 in high yields were observed -when pure bromine and a trace amount of iodine were used, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…We had recently found that 1,3-dibromo-5,5-dimethylhydantoin (DBDH) was able to act as a thiophilic activator to convert acyclic sugar dithioacetals into the alkyl glycofuranosides [40] and envisioned that DBDH, a cheap source for in situ generation of bromonium ion, might be a useful catalyst for the activation of sulfide to activate the dithioacetals in the presence of cyclic glycosyl acceptors towards the formation of acyclic glycosylidene acetals. DBDH has so far been utilized mainly as a free radical brominating agent [41] and as a source of bromonium ion, exploited in aromatic ring brominations, [42,43] but the full versatility of this reagent has not been well investigated. After a series of experiments regarding the quantity of activator, reaction solvent and other conditions, it was established that the use of 1.5 equivalent of DBDH was able to provide successful coupling of acyclic donors with the cyclic sugar derivatives through an acetal linkage at 0°C in CH 3 CN as solvent in a very short period of time and in excellent yields (Scheme 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Me-80BA was synthesized from o-cresol by etherification with octyl bromide and regioselective bromination of aromatic ring [12] followed by the 275…”
Section: Syntheses Of Benzoic Acid Derivatives and Amentioning
confidence: 99%